2022
DOI: 10.1101/2022.12.04.519031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Local Analysis deconstructs protein - protein interfaces and accurately estimates binding affinity changes upon mutation

Abstract: The spectacular recent advances in protein and protein complex structure prediction hold promise for reconstructing interactomes at large scale and residue resolution. Beyond determining the 3D arrangement of interacting partners, modeling approaches should be able to unravel the impact of sequence variations on the strength of the association. In this work, we report on Deep Local Analysis (DLA), a novel and efficient deep learning framework that relies on a strikingly simple deconstruction of protein interfa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…TopNetTree, a recent deep learning approach, includes physical pairwise interactions, Euclidean distances, and cavity structures within a topological framework. Notably, TopNetTree has been actively used in numerous SARS-CoV-2 studies[46,50,5254,56]. In particular, Chen et al, trained TopNetTree on SARS-CoV-2 datasets to accurately predict changes in binding free energy for the S protein, ACE2, or antibodies induced by mutations[24]This tool was not available as a web server or a standalone tool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TopNetTree, a recent deep learning approach, includes physical pairwise interactions, Euclidean distances, and cavity structures within a topological framework. Notably, TopNetTree has been actively used in numerous SARS-CoV-2 studies[46,50,5254,56]. In particular, Chen et al, trained TopNetTree on SARS-CoV-2 datasets to accurately predict changes in binding free energy for the S protein, ACE2, or antibodies induced by mutations[24]This tool was not available as a web server or a standalone tool.…”
Section: Resultsmentioning
confidence: 99%
“…During recent years, several AI methods have been proposed for predicting mutation-imposed interaction changes [21][22][23][46][47][48]. Among these tools, we concentrated on two, mmCSM-PPI [22] and TopNetTree [23,24], of which results on the RBD-ACE2 system were readily available.…”
Section: Volume and Hydrophobicity Biases Are The Most Obvious Mispre...mentioning
confidence: 99%
“…In recent years, several AI methods have been proposed for predicting mutation-imposed interaction changes. [21][22][23][46][47][48] Among these tools, we concentrated on two, mmCSM-PPI 22 and TopNetTree, 23,24 of which results on the RBD-ACE2 system were readily available. 24,[49][50][51][52][53][54][55][56] The machine learning approach, mmCSM-PPI, utilizes physicochemical and geometrical properties of protein structures within a graphbased structural framework to model the impact of mutations on the inter-residue interaction network.…”
Section: Can Ai Methods Perform Better Than the Classical Techniques?mentioning
confidence: 99%
“…Since then, we observed that the additional set of sequences had a limited impact on the performance (average ∆ρ = 0.012 on the dataset reported (Hopf et al, 2017)). Hence, in more recent studies (Tsuboyama et al, 2023;Mohseni Behbahani et al, 2023), we solely relied on an input alignment generated with the ProteinGym-MSA protocol. In the present work, for all calculations, we asked GEMME to exploit only a single input MSA generated by one of the four tested protocols and resources (see Additional file 1: Supplementary Methods for computational details).…”
Section: Gemme Methodology and Usagementioning
confidence: 99%